Interval Training Improves Depressive Symptoms But Not Anxious Symptoms in Healthy Women - Viana, Ricardo Borges; Gentil, Paulo; Naves, João Pedro Araújo; Rebelo, Ana Cristina Silva; Santos, Douglas Assis Teles; Braga, Marco Aurélio Oliveira; de Lira, Claudio Andre Barbosa (Frontiers in Psychiatry, 2019)
Background: Despite important advances in the relationship between exercise and mood disorders, especially regarding moderate intensity continuous training, there is a lack of information about the chronic effects of interval training protocols. We compared the effects of two different interval training protocols (sprint interval training [SIT] and high intensity interval training [HIIT]) on depressive and anxious symptoms in healthy women. Methods: Thirty-six women were randomly allocated to a HIIT (n=18) or SIT (n=18) groups and performed 24 training sessions over eight weeks (thrice a week). Levels of state-trait anxiety and depressive symptoms were evaluated using State–Trait Anxiety Inventory and Beck Depression Inventory, respectively, before and after training intervention. Results: Two-way analysis of variance (ANOVA) did not reveal significant effect of time (p>0.05), group intervention (p>0.05) or time x group interaction (p>0.05) on state-trait anxiety; however, two-way ANOVA showed a significant effect of time on depressive symptoms (p=0.025) but not group effect (p=0.548) or time x group interaction (p=0.373). Depressive symptoms of the participants in both HIIT and SIT group reduced from baseline (ΔHIIT) -17.5±27.9% and (ΔSIT) -28.6±47.5%, respectively. Conclusion: HIIT and SIT groups similarly improved depressive symptoms but not anxiety levels in healthy and physically active young adult women.